Management characteristics and prognosis after stroke in China: findings from a large nationwide stroke registry - Qin, H; Chen, Y; Liu, G; Turnbull, I; Zhang, R; Li, Z; Wang, Y; Liu, L; Zhao, X; Chen, Z; Wang, Y (BMJ Publishing Group, 2020)
Background and purpose There is limited nationwide evidence about the standard management characteristics of stroke types and prognosis in China. This study aimed to assess clinical characteristics, in-hospital and after-discharge management characteristics and prognosis for stroke types in China.